AI-Enhanced Prediction of Reinforcement Steel Corrosion in Coastal Concrete Structures in Yemen Using a Hybrid Protection System - Al-shameri, Mohammed Hael; Khaled, Amgad S. D.; Al-qahtani, Anees M.; AL Ahdal, Ammar (مجـلـة جـامـعـة السـعيد للعلـوم التطبيقية, 2025)
The corrosion of reinforcement steel poses a significant threat to the longevity of concrete structures in Yemen's harsh coastal conditions. This study presents and tests an AI-enhanced predictive model to evaluate the long-term effectiveness of a novel hybrid protection system that integrates an epoxy coating with Impressed Current Cathodic Protection (ICCP).The model, developed using finite element simulation data adjusted to Yemeni coastal circumstances, predicts corrosion behavior over the structure's lifespan. The findings indicate that the hybrid system decreases the corrosion rate by an average of 68% relative to unprotected structures. This study offers a comprehensive approach for forecasting material durability and substantiates a sustainable engineering solution to prolong the service life of essential infrastructure in the area.